NANO CARBON SYNTHESIS FROM MICROALGAE CHLORELLA VULGARIS AS PRECURSOR OF SOLID PHASE CARBON - Alexander William Prijadi; Arenst Andreas Arie; Budi Husodo Bisowarno (JURNAL INTEGRASI PROSES, 2022)
Nanocarbon is a nanometer-scale substance made entirely of carbon atoms. Generally, the synthesis of nanocarbon is usually conducted using a gas-phase carbon raw material which is toxic. Therefore, the use of solid-phase carbon raw material to synthesize nanocarbon started to develop. In this research, nanocarbon will be synthesized using variations of solid-phase carbon raw material derived from a novel carbon precursor, microalgae Chlorella vulgaris. Nanocarbons produced were analyzed using SEM, XRD, and TEM. SEM analysis did not show the nanocarbon formed. However, this may be due to the nanocarbon being very small. To ensure whether nanocarbon is formed or not, XRD analysis is conducted. XRD analysis shows the possibility of forming carbon nanotubes from the sample with activated carbon as a raw material. There were peaks at diffraction angles of 24–26° and 42–43,5°, which indicated carbon nanotubes. In addition, the dc value of this sample has a value like carbon nanotubes, which is 0.344 nm. In contrast, the other two samples, which used hydrochar and microalgae as raw materials, only indicated activated carbon after the synthesis. The TEM analysis supported by XRD analysis for a sample with activated carbon as a raw material showed the presence of carbon nanotubes. This is indicated by their rope-like morphology, which is not visible in SEM analysis due to their tiny size. At the same time, the other two samples did not show any morphology indicating the presence of nanocarbon. So, it can be concluded that the synthesis of nano carbon has been successfully carried out using activated carbon as raw material and produces nano carbon with the type of carbon nanotubes.